PKM Pelatihan Ekonomi Untuk Guru-Guru Anggota MGMP Ekonomi Kabupaten Tanah Datar - Salma Taqwa; Fiola Finomia Honesty; Vanica Serly (Universitas Negeri Padang, 2019)
Teachers as professional educators are responsible as educators and instructors for their students. In order to work well, teachers must have appropriate competencies in the field of study they are teaching. Economic subjects in high school include the economics and accounting fields, which must be mastered by the teacher. The development of economics and accounting must be reached by the economics teacher who will transfer knowledge to their students. Besides that, the teacher's educational background will also affect student learning process. Training for high school economics teachers is needed to be able to increase the insight and knowledge of teachers. MGMP is one of the means for the teachers to draw and explore economics in order to be a professional teachers. From the results of the pretest and posttest, it can be concluded that there was an increasing in teacher knowledge generated from this training. It is expected that in the future MGMP will have a role in training and developing the knowledge of economics teachers in Tanah Datar.Keywords: economics, accounting, educational, teachers